2012
DOI: 10.1103/physrevlett.108.093401
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast X-Ray Scattering of Xenon Nanoparticles: Imaging Transient States of Matter

Abstract: Femtosecond x-ray laser flashes with power densities of up to 10(14) W/cm(2) at 13.7 nm wavelength were scattered by single xenon clusters in the gas phase. Similar to light scattering from atmospheric microparticles, the x-ray diffraction patterns carry information about the optical constants of the objects. However, the high flux of the x-ray laser induces severe transient changes of the electronic configuration, resulting in a tenfold increase of absorption in the developing nanoplasma. The modification in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
95
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(98 citation statements)
references
References 21 publications
3
95
0
Order By: Relevance
“…The core of such large objects expands hydrodynamically due to the growing electron pressure within [17,18]. Theoretical studies predict a * Electronic address: nicusor@xray.bmc.uu.se transition from Coulomb explosion to hydrodynamic expansion with increasing sample size [13].The study of Coulomb explosion of molecular clusters with intense infrared lasers has shown the advantage of using heteronuclear molecules, such as CH 4 or CD 4 , to analyze the dynamics of the explosion [22,23]. In a heteronuclear cluster, the light ions can gain additional energy during the explosion by interacting with multiply charged heavy ions (C n+ ).…”
mentioning
confidence: 99%
“…The core of such large objects expands hydrodynamically due to the growing electron pressure within [17,18]. Theoretical studies predict a * Electronic address: nicusor@xray.bmc.uu.se transition from Coulomb explosion to hydrodynamic expansion with increasing sample size [13].The study of Coulomb explosion of molecular clusters with intense infrared lasers has shown the advantage of using heteronuclear molecules, such as CH 4 or CD 4 , to analyze the dynamics of the explosion [22,23]. In a heteronuclear cluster, the light ions can gain additional energy during the explosion by interacting with multiply charged heavy ions (C n+ ).…”
mentioning
confidence: 99%
“…In fact, standard Mie scattering theory assuming a homogeneous, overdense plasma sphere was used to characterize rare gas clusters in recent experiments on a shot-to-shot basis [7,8]. However, inside such a sphere, standard Mie theory would predict electric fields only within a narrow skin layer while, in this Letter, we will show that a highly inhomogeneous and temporally changing charge density distribution may be created in the droplet interior.…”
mentioning
confidence: 77%
“…Rare gas clusters, bound by easy-to-model van der Waals forces, have traditionally served as testbeds as intense lasers have evolved from optical to x-ray wavelengths [10,38,[57][58][59][60][61][62][63][64]. FEL-induced transient dynamics in rare gas clusters have been observed in imaging experiments in the XUV [65] and, more recently, in the x-ray regime [66] providing evidence for femtosecond time scale electronic damage.…”
Section: Introductionmentioning
confidence: 99%